ジスルフィラムはモデル動物において強力な抗不安様作用・鎮痛作用を示す - 藤塚, 亮次; 重本, 千宙; 山田, 大輔; 太田, 有紗; 吉岡, 寿倫; 寺島, 裕也; 山内, つぐみ; 坂田, 壮太; 松浦, 航太; 中谷, 百伽; 松島, 鋼治; 斎藤, 顕宜 (日本薬理学会年会要旨集, 2022)
Disulfiram (DSF) is an FDA approved drug for the treatment of alcoholism. The drug acts by inhibiting aldehyde dehydrogenase, an enzyme essential to alcohol metabolism. However, a recent study has demonstrated that DSF also potently inhibits the cytoplasmic protein FROUNT, a common regulator of chemokine receptor CCR2 and CCR5 signaling. Several studies have reported that chemokine receptors are associated with the regulation of emotional and pain behaviors in rodents. Therefore, this study was performed to clarify these effects of DSF in rodents. The anxiolytic-like and antinociceptive effects of DSF were investigated using an elevated plus-maze (EPM) test and a formalin test, respectively. DSF significantly increased the amount of time spent in the open arms of the maze without affecting the total open arms entries in the EPM test. Moreover, DSF decreased the duration of pain-related behaviors in the formalin test. However, no effect in both EPM and formalin tests was seen following administration of the selective aldehyde dehydrogenase inhibitor cyanamide. These results suggested that DSF produces anxiolytic-like and antinociceptive effects in rodents. We propose that the inhibitory activity of DSF against FROUNT function provides an effective therapeutic option in anxiety accompanied with pain.